Allopurinol and ellagic acid decrease epileptiform activity and the severity of convulsive behavior in a model of status epilepticus. Issue 2 (20th December 2022) - Pardo-Peña, Kenia; Medina-Ceja, Laura; Martínez-Gallegos, Salvador; Sánchez-Lira, Ana
Abstract : Background: During status epilepticus, severe seizures can occur, generating recurrent cycles of excitotoxicity and oxidative stress that cause neuronal damage and cell death. The administration of agents with antioxidant properties represents a therapeutic alternative aimed at reducing the severity of status epilepticus and mitigating the neurobiological consequences that precede them. Objective: The objective of this work was to evaluate the antiseizure effect of the antioxidants allopurinol (ALL) and ellagic acid during status epilepticus induced by pilocarpine (PILO). Methods: Male Wistar rats (200–250 g) were injected with ALL (50 mg/kg) or ellagic acid (50 mg/kg), 30 min before PILO administration (pretreatment) or 60 min after the beginning of status epilepticus, to evaluate the antiseizure effect of these drugs on epileptiform activity and convulsive behavior. Results: ALL or ellagic acid administration before or after PILO significantly decreased the epileptiform activity and the severity of convulsive behavior. Better efficacy was observed when the drugs were administered as a pretreatment, increasing the latency time of the appearance of status epilepticus from 27.2 ± 2.6 to 45.8 ± 3.31 min, and significantly reducing the amplitude of epileptiform discharges by 53.5% with ALL and 68.9% with ellagic acid. Conclusion: The antioxidants ALL and ellagic acid showed an antiseizure effect, representing an alternative to reduce epileptiform activity and severity of convulsive behavior during status epilepticus, an effect that may be used as adjuvants to mitigate or reduce oxidative damage processes.